Occupational and Leisure Physical Activity on Cardiovascular Risk and Body Composition Among Courier Workers - Galmes-Panades, Aina Maria; Abbate, Manuela; Bennasar-Veny, Miquel; Lopez-Gonzalez, Angel Arturo; Vicente-Herrero, Mª Teofila; Busquets-Cortes, Carla; Leiva, A.; Yanez, Aina Maria (Biological Research For Nursing, 2023)
Objective There is some controversy about the beneficial effects of occupational physical activity (OPA) on cardiovascular risk (CVR). The main aim of this study was to explore the effect of the combination of different frequencies of leisure-time physical activity (LTPA) and two types of OPA on CVR and body composition, and whether the association between physical activity (PA) and CVR was mediated by visceral adipose tissue (VAT). Methods This cross-sectional study included data from 2516 couriers living in Spain, delivering either by motorbike or foot, and practicing LTPA never, occasionally, or regularly. Couriers were classified into six categories according to LTPA and OPA; body composition was assessed by Bioelectrical Impedance, and CVR by the Framingham equation. General linear models were performed to explore the association between different categories with each outcome (CVR and body composition) and the possible role of VAT as a mediator between PA and CVR. Results Compared with the most sedentary group (motorbike couriers that never practice PA), walking couriers who practice regular PA presented the lowest CVR [beta -1.58 (95% CI -2.31; -0.85)] and the lowest VAT [beta -2.86 (95% CI -3.74; -1.98) followed by the motorbike couriers who practiced regular PA [beta -0.51 (95% CI -1.00; -0.03) for CVR and beta -2.33 (95% CI -2.91; -1.75) for VAT]. The association between PA and CVR was partially mediated by VAT. Conclusion The present results indicated that both OPA and LTPA are protective factors for CVR and play an important role on VAT accumulation.
Keywords: occupational physical activity; leisure-time physical activity; cardiovascular disease risk; visceral adipose tissue; total body fat; total muscle mass; JCR; Scopus